Assessment of Fresh Milk Quality Through Quality Parameters: Assessment of Fresh Milk Quality - Ibrahim, Tanveer; Wattoo, Feroza Hamid; Sarwar Wattoo, Muhammad Hamid; Hamid, Saima (Pakistan Journal of Health Sciences, 2023)
Raw milk manipulation is one of the major food frauds to gain financial benefits that can be identified through basic analysis. Objective: To analyse fresh milk quality parameters not only to define that milk is of poor quality but also to give some sort of clue that milk is adulterated. Methods: In this regard, a total of 110 (47 cows and 63 buffalo) raw milk samples were collected along with control samples through recommended methods and their routine physical & chemical quality parameters were analyzed. Results: The analysis of physical & chemical quality parameters showed 52/110 (47.3%) unsatisfactory samples with significantly decreased levels of major quality parameters like milk fat (94.2%), total solids (90.4%) and specific gravity (75.0%). It also showed an addition of water while other parameters were comparatively less decreased. There was compensation of water with thorough addition of other adulterants. The analysis also showed 58 (52.7%) samples were found satisfactory with 41/58 (70.7%) samples having normal quality parameters showing natural raw milk or precisely prepared adulterated milk while 17/58 (29.3%) samples had exceptionally raised quality parameters as fat 16/17 (94.1%) samples, total solids 14/17 (82.4%) and specific gravity 12/17 (70.6%) of samples showed the addition of water as well as other adulterants. Conclusions: The assessment of the quality of fresh milk through physical and chemical parameters not only described the poor quality of fresh milk but also gave some clues regarding the addition of different sorts of adulterants (>76.6%).